1971
DOI: 10.1002/neu.480020307
|View full text |Cite
|
Sign up to set email alerts
|

Influence of lanthanum on transmitter release at the neuromuscular junction

Abstract: SUMMARYThe presynaptic influence of lanthanum on neuromuscular transmission was studied in the isolated sciatic nerve-sartorius muscle preparation of the frog, Rana pipiens. Twitch tension output from indirectly stimulated muscles progressively decreased with increasing concentrations of La3+ from 0.01 t o 1.0 mM and was abolished in the presence of 0.5 mM and 1 mM LaR+ after approximately 50 min and 15 min, respectively. Studies on directly stimulated muscle indicated that the inhibition by La3 + of tension d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
0

Year Published

1973
1973
1990
1990

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(18 citation statements)
references
References 32 publications
2
16
0
Order By: Relevance
“…It was pointed out by Lettvin, Pickard, McCulloch & Pitts (1964) that Ca2+ and La3+ have roughly similar radii, but that with its higher valence La3+ might be bound much more strongly at some sites; it was verified that in terms of nerve blocking La3+ acts as if it were equivalent to an extraordinarily high Ca2+ concentration (Takata, Pickard, Lettvin & Moore, 1966). At the neuromuscular junction, Blioch, Glagoleva, Liberman & Nenashev (1968) found La3+ to be much more effective than divalent cations in increasing the frequency of miniature end-plate potentials (m.e.p.p.s), a result confirmed by Heuser & Miledi (1971) and DeBassio, Schnitzler & Parsons (1971), and suggested that La3+ might enter the terminal in the same way as Ca2+ and subsequently activate the release process. In agreement with this hypothesis Blioch et al (1968) also reported a small increase of quantal contents of end-plate potentials (e.p.p.s) with La3 , in nominally Ca2+-free solution, but Miledi (1966but Miledi ( , 1971, Heuser & Miledi (1971) and DeBassio et al (1971) found only a profound depression of the e.p.p.…”
Section: Introductionsupporting
confidence: 66%
See 1 more Smart Citation
“…It was pointed out by Lettvin, Pickard, McCulloch & Pitts (1964) that Ca2+ and La3+ have roughly similar radii, but that with its higher valence La3+ might be bound much more strongly at some sites; it was verified that in terms of nerve blocking La3+ acts as if it were equivalent to an extraordinarily high Ca2+ concentration (Takata, Pickard, Lettvin & Moore, 1966). At the neuromuscular junction, Blioch, Glagoleva, Liberman & Nenashev (1968) found La3+ to be much more effective than divalent cations in increasing the frequency of miniature end-plate potentials (m.e.p.p.s), a result confirmed by Heuser & Miledi (1971) and DeBassio, Schnitzler & Parsons (1971), and suggested that La3+ might enter the terminal in the same way as Ca2+ and subsequently activate the release process. In agreement with this hypothesis Blioch et al (1968) also reported a small increase of quantal contents of end-plate potentials (e.p.p.s) with La3 , in nominally Ca2+-free solution, but Miledi (1966but Miledi ( , 1971, Heuser & Miledi (1971) and DeBassio et al (1971) found only a profound depression of the e.p.p.…”
Section: Introductionsupporting
confidence: 66%
“…At the neuromuscular junction, Blioch, Glagoleva, Liberman & Nenashev (1968) found La3+ to be much more effective than divalent cations in increasing the frequency of miniature end-plate potentials (m.e.p.p.s), a result confirmed by Heuser & Miledi (1971) and DeBassio, Schnitzler & Parsons (1971), and suggested that La3+ might enter the terminal in the same way as Ca2+ and subsequently activate the release process. In agreement with this hypothesis Blioch et al (1968) also reported a small increase of quantal contents of end-plate potentials (e.p.p.s) with La3 , in nominally Ca2+-free solution, but Miledi (1966but Miledi ( , 1971, Heuser & Miledi (1971) and DeBassio et al (1971) found only a profound depression of the e.p.p. by La3+. It is notable, however, that La3+ appears to be essentially irreversible as an activator of release; the fall in m.e.p.p.…”
Section: Introductionsupporting
confidence: 54%
“…e.p.p.s at normal motor end-plates (deBassio, Schnitzler & Parsons, 1971;Heuser & Miledi, 1971), whereas even greater concentrations have no apparent effect on the frequency of 'Schwann min. e.p.p.s' in denervated muscles (Bevan, Grampp & Miledi, 1973;Dennis & Miledi, 1974a).…”
Section: Calcium-dependence Of Transmitter Releasementioning
confidence: 99%
“…Strontium (Miledi, 1966;Dodge, Miledi & Rahamimoff, 1969;Meiri & Rahamimoff, 1971) and, to some extent, Ba (Miledi, 1966) appear to be able to restore transmitter release in neuromuscular junctions in which transmission has been blocked by bathing the preparation in Ca-free Ringer solution. On the other hand, Mg2+, Co2+, Ni2+, Ml2+, CU2+, Zn2+, Cs2+, LaO+, and Cr3+ were found to be ineffective in replacing Ca2+, and they inhibited transmitter release when added to Ringer solution containing Ca2+ (del Castillo & Engbaek, 1954;del Castillo & Katz, 1954a;Miledi, 1966; Mambrini & Benoit, 1969;Benoit & Mambrini, 1970;Heuser & Miledi, 1971;Meiri & Rahamimoff, 1971; DeBassio, Schnitzler & Parsons, 1972;Balnave & Gage, 1973;but compare Blioch, Glagoleva, Liberman & Nenashev, 1968). The antagonism between Ca and Mg (Jenkinson, 1957;Doge & Rahamimoff, 1967;Hubbard, Jones & Landau, 1968) and between Ca and Mn (Meiri & Rahamimoff, 1972;Balnave & Gage, 1973) in the release mechanism has been shown to be competitive in nature.…”
Section: Introductionmentioning
confidence: 99%